The Effect Of Teacher Performance Assessment And Compensation On Teacher Professionalism At UPTD SD District Of Galis Bangkalan - Yumi Ida (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2023)
This article aims to explain the effect of Performance Assessment and Compensation on the Professionalism of Elementary School teachers in the Galis Bangkalan District. This is based on the researcher's anxiety about whether teacher professionalism is affected by pragmatic things such as; performance appraisal and compensation go beyond their oath as educators. The method used is a quantitative method with multiple regression types. Data collection was carried out using a questionnaire. Data analysis used descriptive statistical analysis with the help of SPSS for windows version 22. The results of the analysis show that 1) Performance Assessment has a positive and significant effect on Teacher Professionalism, 2) Compensation has a positive and significant effect on Teacher Teacher Professionalism, and 3) Performance Assessment and compensation has a positive and significant effect on the Professionalism of Elementary School teachers in the Galis District with an F count of 32.086 with a p-value of 0.000 less than 0.05. This means that the increase in performance appraisal and teacher compensation will simultaneously affect the increase in teacher professionalism